The Reality of The Innovative Product and Its Role in Improving the Demand for Insurance Services from The Point of View of Insurance Company Clients in The Syrian Coast ) Field Study( (Journal of Hama University, 2022)
The research aimed to determine the role of the innovative product as an independent variable in its two dimensions (introducing a new product, developing the current product) and its role in improving the demand for insurance services provided as a dependent variable. Lattakia and Tartous which are able to subscribe to insurance policies, and the researcher relied on choosing a simple random sample representing the studied community, and 433 questionnaires were obtained. Insurance services to a greater degree, compared to improving the existing products that already exist. There is demand for insurance services and technology adoption and social networking sites with the aim of facilitating and rapid dissemination among the general public, and working on pricing insurance services, especially new ones, according to ways and methods that are considered and appropriate to the citizen’s income and the living conditions that the country is going through